Kłamstwo jako przedmiot badań jakościowych. Ograniczenia i możliwości = A lie as the subject of quality research. Limitations and possibilities - Surmiak, Adrianna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Quality sociologists and culture anthropologists comparatively rarely examine the question of a lie. It is more often the concern of research by psychologists mainly by means of quantity methods. It seems to be resulting from some difficulties in the research itself which is connected with the accurate recognition of a lie.
Keywords: kłamstwo; badania jakościowe; socjologia; antropologia kulturowa